Financial access, financial literature, and financial experience and the impact on MSMEs' financial behavior - Franky Okto Bernando; Pringgondani (Jurnal Mantik, 2023)
The Gross Domestic Product (GDP) of Indonesia is made up of 60.6% MSMEs. On the other hand, there are still many MSME players who lack access to financial institutions and have poor levels of financial awareness and experience. This study aims to ascertain whether there is a relationship between financial access (X1), financial literacy (X2), and financial experience (X3) and SMEs' financial behavior (Y). The financial behavior (X1) Y variable was significantly influenced by the variables of financial access (X1), financial literacy (X2), and financial experience (X3). The value of the coefficient of determination in Adjusted R Square explains the magnitude of the influence to the extent of 72.8%, while the remaining 27.2% is influenced by b. The research data was tested using SPSS version 25, and the results of the study both partially using the T test and simultaneously using the F test.